Rural Trends in Diagnosis and Services for Autism Spectrum Disorder - Antezana, Ligia; Scarpa, Angela; Valdespino, Andrew; Albright, Jordan; Richey, John A. (Frontiers in Psychology, 2017)
Rural communities face significant challenges regarding the adequate availability of diagnostic-, treatment-, and support-services for individuals with autism spectrum disorder (ASD). Specifically, a variety of factors, including geographic distance between families and service providers, low reliance on health care professionals, and cultural characteristics, contribute to the diminished availability and utilization of services. Together, these factors lead to risks for delayed ASD screening and diagnosis, yielding lower educational and functional outcomes. The purpose of this review is to outline the specific diagnosis and treatment barriers that affect individuals with ASD and their families in rural settings. Telehealth feasibility and efficacy research is also reviewed, suggesting that telecommunication services may offer an inroad for addressing the specific service barriers faced by rural communities. Together, the current review identifies specific needs for both research and support services that address the specific access barriers characteristic of rural settings.